Fracture behavior of Inconel 718 sheet in thermal-aided deformation considering grain size effect and strain rate influence. (15th September 2017) - Zhao, R.; Li, X.J.; Wan, M.; Han, J.Q.; Meng, B.; Cai, Z.Y.
Abstract: In this paper, the fracture behavior of Inconel 718 sheets in thermal-aided deformation processes is elucidated, accompanied by high-temperature fracture photography analysis, considering the effect of grain size and strain rate. Uniaxial tests were conducted under varied test conditions. A segmentation phenomenon was observed in the Hall-Petch curves for the fracture stress at lower strain rates, which disappeared at higher strain rates. Moreover, the fracture strain is predicted by the Cockcroft & Latham criterion with a modified Voce constitutive model. Based on the fracture photographs acquired by scanning electron microscopy (SEM), a two-step fracture mechanism was proposed and shown for Inconel 718 thin sheets. Furthermore, thin sheet fracture was found to be influenced by inclusions, which was verified by CAE simulations. This article thus provides an in-depth discussion of fracture behavior of Inconel 718 thin sheets, which was influenced by the comprehensive effects of the grain size distribution, strain rate influence, local element composition, and the second-phase particles or inclusions. Graphical abstract: Highlights: Segmentation of Hall-Petch curve of fracture stress is 0.13μm -1/2 under 0.001s -1 and disappears at higher strain rate. Fracture strain is predicted by Cockcroft & Latham criterion with a modified Voce constitutive model. Subsequent transgranular/intergranular fracture occurs after the initial intergranular fracture of Inconel 718 thin sheet. NbC and TiC carbides, harder than matrix, denoted the preferential locations for dimples and weak areas for fracture.